Spontaneously conceived heterotopic pregnancy with abdominal pregnancy implanted on the vesicouterine pouch: A case report and literature review. Issue 10 (3rd August 2021) - Ozawa, Nobuaki; Shibata, Megumi; Mitsui, Mari; Umehara, Nagayoshi; Samura, Osamu; Sago, Haruhiko
Abstract: We report the case of a 36‐year‐old woman with spontaneously conceived heterotopic pregnancy with abdominal pregnancy. She visited the hospital at 5 weeks and 4 days of gestation and transvaginal ultrasonography revealed a normal intrauterine pregnancy. Two days later, she was urgently transported to the hospital due to extreme abdominal pain. Emergent laparotomy was performed to investigate the cause of massive intraperitoneal bleeding, which was confirmed to have been due to an abdominal pregnancy that implanted on the vesicouterine pouch. The hematic mass, including chorionic villi, was successfully removed from the peritoneum. The subsequent course of the intrauterine pregnancy was uneventful and a healthy baby was born at term. To the best of our knowledge, this is an extremely rare case report of a spontaneously conceived heterotopic abdominal pregnancy, in which the intrauterine pregnancy showed a successful outcome despite the collapse of the abdominal pregnancy at a very early stage.